Changes in basic meanings from Proto-Austronesian to Acehnese - Dohra Fitrisia; Dwi Widayati (Universitas Syiah Kuala, 2018)
Changes in meaning or semantic changes are the area of diachronic linguistics. The Acehnese language is a derivative of the Proto-Austronesian (PAN) language that has had changes in the meaning of its lexicon that have become the object of this interesting study. It is aimed at explaining examples of changes in meaning in the Acehnese etynom based on four basic types of changes of meaning categorized according to Crowley and Bowern (2010). The data was taken from the English Finder list of Reconstruction in Austronesian Languages reconstructed (Wurm Wilson, 1975). The selected data from the results of this study was then confirmed by six native speakers' expert in the actual use of the Acehnese language. The results showed that some original meanings from PAN have become broader, some narrower, some have bifurcated and some have shifted in meaning.